James Madison : a life reconsidered - Cheney, Lynne V. (Viking, 2014)
"This majestic new biography of James Madison explores the astonishing story of a man of vaunted modesty who audaciously changed the world. Among the Founding Fathers, Madison was a true genius of the early republic. Outwardly reserved, Madison was the intellectual driving force behind the Constitution and crucial to its ratification. His visionary political philosophy and rationale for the union of states--so eloquently presented in The Federalist papers--helped shape the country Americans live in today. Along with Thomas Jefferson, Madison would found the first political party in the country's history--the Democratic Republicans. As Jefferson's secretary of state, he managed the Louisiana Purchase, doubling the size of the United States. As president, Madison led the country in its first war under the Constitution, the War of 1812. Without precedent to guide him, he would demonstrate that a republic could defend its honor and independence--and remain a republic still"--